The top job - Kimmel, Elizabeth Cody.; Neubecker, Robert (New York, N.Y. : Dutton Children's Books, 2007)
On Career Day, a young girl entertains the class with a description of her father's exciting job as light bulb changer at the top of the Empire State Building.
A Junior Library Guild selection
Keywords: Empire State Building (New York, N.Y.) -- Juvenile fiction; Empire State Building (New York, N.Y.) -- Fiction; Occupations -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Occupations -- Fiction; Fathers and daughters -- Fiction; New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction